(untitled) (International Journal of Culture and Art Studies, 2024)
The representation of Fancy Dress masquerades in Ghana, particularly in Winneba, has been revered as part of the countryâ€™s popular culture. Fancy Dress masquerade performances, which originated in coastal towns of Ghana during the 18th century under the aegis of colonialism, are currently seen in popular parades and club competitions. Undoubtedly, the utilisation of costumes forms the cornerstone of Fancy Dress masquerading. Although Fancy Dress masquerade costumes add to the depth and breadth of the performance, little empirical study exists on the materials used to construct costumes for this performance. In this study, we exploreÂ materials used to construct Fancy Dress masquerade costumes in Winneba, Ghana, from 1958 to 2020. Using a qualitative approach, multiple instruments, and engaging thematic and document analytical frames to analyse the data, the findings of the study revealed the use of fabrics; leather and jute bags. The rest were foam; agricultural products; paper, strawboards and used packaging boxes; net, fibre and plastic sachets to construct costumes such as â€˜cowboyâ€™, â€˜tigersâ€™ and â€˜huntersâ€™. With a treasure trove of materials, fabrics were chiefly used due to their unique physical properties. On the heels of the finding, we recommend that practitioners explore non-conventional and sustainable materials to maintain ecological sustainability. Ultimately, the study advances the understanding of masquerade costumes by addressing gaps in the literature and providing new perspectives.